Multicenter Evaluation of HemoTypeSC as a Point-of-Care Sickle Cell Disease Rapid Diagnostic Test for Newborns and Adults Across India. Issue 1 (1st August 2019) - Mukherjee, Malay B; Colah, Roshan B; Mehta, Pallavi R; Shinde, Nikhil; Jain, Dipty; Desai, Shrey; Dave, Kapilkumar; Italia, Yazdi; Raicha, Bhavesh; Serrao, Erik
Abstract: Objectives: Sickle cell anemia is the commonest genetic disorder in India, and the frequency of the sickle cell gene is very high in the remote tribal areas where facilities are generally limited. Therefore, a rapid and affordable point-of-care test for sickle cell disease is needed. Methods: The diagnostic accuracy of HemoTypeSC was evaluated against automated high-performance liquid chromatography (HPLC) as the gold standard for its efficacy in a newborn screening program. Results: A total of 1, 559 individuals (980 newborns and 579 adults) from four participating centers were analyzed by both methods. HemoTypeSC correctly identified 209 of 211 total hemoglobin (Hb) SS cases, for a 99.1%/99.9% total HbSS sensitivity/specificity. Overall, HemoTypeSC exhibited sensitivity and specificity of 98.1% and 99.1% for all possible phenotypes (HbAA, HbAS, and HbSS) detected. HPLC is relatively expensive and not available in most laboratories in remote tribal areas. Conclusions: We conclude that the rapid, point-of-care testing device HemoTypeSC test is suitable for population and newborn screening for the HbS phenotype.